Dysregulation of the causative genes for hereditary parkinsonism in the midbrain in Parkinson's disease. Issue 8 (26th May 2017) - Kim, Yun Joong; Jeon, Junbeom; Shin, Jaemoon; Kim, Nan Young; Hong, Jeong Hoon; Oh, Jae‐Min; Hong, SangKyoon; Kim, Yeo Jin; Kim, Young‐Eun; Kang, Suk Yun; Ma, Hyeo‐Il; Lee, Unjoo; et al.
ABSTRACT: Background and Objectives: Many hereditary movement disorders with complex phenotypes without a locus symbol prefix for familial PD present as parkinsonism; however, the dysregulation of genes associated with these phenotypes in the SNpc of PD patients has not been systematically studied. Methods: Gene set enrichment analyses were performed using 10 previously published genome‐wide expression datasets obtained by laser‐captured microdissection of pigmented neurons in the SNpc. A custom‐curated gene set for hereditary parkinsonism consisting of causative genes (n = 78) related to disorders with a parkinsonism phenotype, but not necessarily idiopathic or monogenic PD, was constructed from the Online Mendelian Inheritance in Man database. Results: In 9 of the 10 gene expression data sets, gene set enrichment analysis showed that the disease‐causing genes for hereditary parkinsonism were downregulated in the SNpc in PD patients compared to controls (nominal P values <0.05 in five studies). Among the 63 leading edge subset genes representing downregulated genes in PD, 79.4% were genes without a locus symbol prefix for familial PD. A meta–gene set enrichment analysis performed with a random‐effect model showed an association between the gene set for hereditary parkinsonism and PD with a negative normalized enrichment score value (–1.40; 95% CI: –1.52∼–1.28; P < 6.2E‐05). Conclusion: Disease‐causing genes with a parkinsonism phenotype are downregulated in the SNpc in PD. Our study highlights the importance of genes associated with hereditary movement disorders with parkinsonism in understanding the pathogenesis of PD. © 2017 International Parkinson and Movement Disorder Society